EVALUATION TECHNIQUE FOR INFORMATIVE VALUE OF DIAGNOSTIC TESTS IN ANESTHESIOLOGY AND INTENSIVE CARE - A. V. Boyarkina; A. L. Potapov (Вестник анестезиологии и реаниматологии, 2017)
The statistic rates describing the accuracy of diagnostic techniques and their combination have been analyzed including sensitivity, specificity, positive and negative prognostic value, plausibility relation. The best evaluation technique for diagnostic test accuracy at present has been studied, i.e. building up ROC-curve and evaluation of the area under it (Area Under Curve). Advantages and deficiencies of each test have been presented, and their use in the clinical practice has been described.